Bleach. 03, Memories in the rain - Kubo, Tite (Kubo, Tite. Bleach (VIZ Media), 2004)
Ichigo Kurosaki was a little boy when his mother passed away. One rainy day, Ichigo, whose ability to see the undead is a blessing and a curse, tried to stop a young girl from drowning in a nearby river. His mother, Masaki, ran after them, frantically trying to rescue her only son. Then everything went black, and Ichigo awoke only to discover his mother dead and the little girl gone. It's the anniversary of Masaki's death, and the entire Kurosaki clan, along with former Soul Reaper Rukia Kuchiki, head to the cemetery to pay their respects. Sleeping demons rarely ever stay still and pretty soon Ichigo confronts the Grand Fisher, the Hollow that may be responsible for his mother's demise.